1996
DOI: 10.1128/mcb.16.3.1115
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Tumorigenicity and Invasion-Metastasis by Hepatocyte Growth Factor/Scatter Factor-Met Signalling in Human Cells Concomitant with Induction of the Urokinase Proteolysis Network

Abstract: Hepatocyte growth factor/scatter factor (HGF/SF) is a pleiotropic effector of cells expressing the Met tyrosine kinase receptor. Although HGF/SF is synthesized by mesenchymal cells and acts predominantly on epithelial cells, we have recently demonstrated that human sarcoma cell lines often inappropriately express high levels of Met and respond mitogenically to HGF/SF. In the present report we show that HGF/SF-Met signalling in the human leiomyosarcoma cell line SK-LMS-1 enhances its in vivo tumorigenicity, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
238
1
1

Year Published

1998
1998
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 299 publications
(246 citation statements)
references
References 46 publications
6
238
1
1
Order By: Relevance
“…At least two mechanisms are involved in the etiology of these cancers: mutation of the Met receptor to activate the receptor independent of ligand , and coexpression of Met and HGF/SF to establish a transforming autocrine/paracrine growth loop (Je ers et al, 1996b;Rong et al, 1993aRong et al, ,b, 1994. The former mechanism is important in the generation of both inherited and spontaneous forms of papillary renal carcinoma , while the latter mechanism may be causative in a wide variety of malignant diseases, such as sarcomas (Rong et al, 1993a), carcinomas (Je ers et al, 1996c), melanomas (Saitoh et al, 1994), glioblastoma (Koochekpour et al, 1997;Laterra et al, 1997), and even multiple myeloma (Borset et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At least two mechanisms are involved in the etiology of these cancers: mutation of the Met receptor to activate the receptor independent of ligand , and coexpression of Met and HGF/SF to establish a transforming autocrine/paracrine growth loop (Je ers et al, 1996b;Rong et al, 1993aRong et al, ,b, 1994. The former mechanism is important in the generation of both inherited and spontaneous forms of papillary renal carcinoma , while the latter mechanism may be causative in a wide variety of malignant diseases, such as sarcomas (Rong et al, 1993a), carcinomas (Je ers et al, 1996c), melanomas (Saitoh et al, 1994), glioblastoma (Koochekpour et al, 1997;Laterra et al, 1997), and even multiple myeloma (Borset et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…These cells normally produce high levels of Met but virtually no HGF/SF, and in addition, they are non-metastatic and only weakly tumorigenic in nude mice. However, when they stably express exogenous HGF/SF generating an autocrine Met signaling loop, the cells grow much more rapidly in vitro, form colonies in soft agar and display branching morphogenesis in matrigel cultures, all of which underscore their increased propensity to form tumors in nude mice and to metastasize (Je ers et al, 1996b). For di erential display screening, we compared cDNAs isolated from parental SK-LMS cells to those isolated from a pool of SK-LMS cells stably expressing exogenous HGF/SF; cDNA fragments that were di erentially displayed in the initial screening (data not shown) were then used as probes for Northern analyses to verify the expression patterns ( Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HGF decreases cadherin-mediated adhesiveness (Watabe et al, 1993;Shibamoto et al, 1994;Tannapfel et al, 1994;Nabeshima et al, 1998), enhances cell-matrix interaction through the recruitment of integrins, p125 FAK , and paxillin into focal adhesion complexes and concomitant protein phosphorylation of p125 and paxillin (Matsumoto et al, 1994;Jiang et al, 1996). HGF stimulates proteolytic breakdown of the extracellular matrix, through enhancing matrix methaloproteinases (MMPs) and urokinase-type plasminogen activator (uPA)-dependent proteolytic network (Pepper et al, 1992;Jeffers et al, 1996;Date et al, 1998;Kadono et al, 1998;Rosenthal et al, 1998). On the other hand, we found that NK4 inhibits scattering, migration and invasion of SUIT-2 cells, induced by HGF, cocultured fibroblasts and ascitic fluid obtained from patients who underwent pancreatic cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has shown that HGF plays a distinct role in tumour-stromal interactions (Seslar et al, 1993;Rosen et al, 1994;Matsumoto et al, 1996;Inoue et al, 1997;Nakamura et al, 1997;Jiang et al, 1999). HGF has potent motogenic activity on various types of carcinoma cells, leading to the dissociation, scattering and migration of cells (Weidner et al, 1990;Jiang et al, 1993Jiang et al, , 1999Matsumoto et al, 1994Matsumoto et al, , 1996Jeffers et al, 1996;Rosen et al, 1996;Inoue et al, 1997;Nakamura et al, 1997).…”
mentioning
confidence: 99%